Asparaginyl Endopeptidase (Legumain) Supports Human Th1 Induction via Cathepsin L-Mediated Intracellular C3 Activation - Freeley, Simon; Cardone, John; Günther, Sira C.; West, Erin E.; Reinheckel, Thomas; Watts, Colin; Kemper, Claudia; Kolev, Martin V. (Frontiers in Immunology, 2018)
Autocrine activation of the complement receptors C3aR and CD46 by complement activation components C3a and C3b produced through C3 cleavage by the protease cathepsin L (CTSL) during T cell stimulation is a requirement for IFN-γ production and Th1 induction in human CD4+ T cells. Thus, lack of autocrine CD46 activation, such as in CD46-deficient patients, is associated with defective Th1 responses and recurrent infections. We have identified LGMN [the gene coding for legumain, also known as asparaginyl endopeptidase (AEP)] as one of the key genes induced by CD46 co-stimulation during human CD4+ T cell activation. AEP processes and activates a range of proteins, among those α1-thymosin and CTSL, which both drive intrinsically Th1 activity—but has so far not been described to be functionally active in human T cells. Here we found that pharmacological inhibition of AEP during activation of human CD4+ T cells reduced CTSL activation and the CTSL-mediated generation of intracellular C3a. This translated into a specific reduction of IFN-γ production without affecting cell proliferation or survival. In line with these findings, CD4+ T cells isolated from Lgmn−/− mice also displayed a specific defect in IFN-γ secretion and Th1 induction. Furthermore, we did not observe a role for AEP-driven autocrine α1-thymosin activation in T cell-derived IFN-γ production. These data suggest that AEP is an “upstream” activator of the CTSL-C3-IFN-γ axis in human CD4+ T cells and hence an important supporter of human Th1 induction.